2011
DOI: 10.1097/sle.0b013e318217640a
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Fistulization of a Pancreatic Abscess to Colon and Duodenum Treated With Percutaneous Drainage

Abstract: Pancreatic fistulas are rare clinical entities associated with severe pancreatitis. A 39-year-old man who had been diagnosed and treated for severe pancreatitis 2 months ago presented with abdominal pain, fever, and vomiting. The abdominal computed tomography (CT) demonstrated a peripancreatic abscess and a duodenal fistula communicating the first part of duodenum, which was also verified with fluoroscopy. A size 14-French catheter with pig-tail tip was inserted primarily with a Seldinger 2-step technique thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Hwang et al, have reported closing the fi stula hole endoscopically using hemoclips and biological glue with good outcome [15]. Sezer et al, reported percutaneous drainage of pancreatic abcess which was fi stulized in the ascending colon [18]. Nevertheless, all these techniques are feasible for only well-defi ned pseudocyst or collection and by an experienced operator.…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al, have reported closing the fi stula hole endoscopically using hemoclips and biological glue with good outcome [15]. Sezer et al, reported percutaneous drainage of pancreatic abcess which was fi stulized in the ascending colon [18]. Nevertheless, all these techniques are feasible for only well-defi ned pseudocyst or collection and by an experienced operator.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory process of acute pancreatitis may lead internal fistulization to the GI tract. 10 Spontaneous pancreaticoduodenal fistulas are not uncommon; depending on the study population, the incidence varies from 3% to 47%. 11 - 14 Duodenal and colonic fistulas occur more frequently compared to other sites due to their anatomic proximity.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional management of pancreatoenteric fistulas and pancreatic abscess with aggressive surgery or percutaneous drainage catheter placement are associated with increased surgery-related morbidity and mortality, and a longer hospitalization. 3 , 4 , 7 , 8 Though the peripancreatic abscess may be addressed by various drainage methods the complete closure of the entire fistula remains difficult. Recently, a variety of occlusion methods of external or internal pancreatic fistula are reported with minimally invasive techniques such as endoscopy and fibrin glue sealant.…”
Section: Discussionmentioning
confidence: 99%